The lawman's surprise - Mann, Catherine (Harlequin special edition, 2023)
Her troubled teenage brother just brought Sheriff Declan Winslow back into Charlotte Pace's life. Their brief fling ended three months ago, but Charlotte can't keep her pregnancy a secret much longer. Nor can she afford their attraction to surface again when she and Declan seek shelter during a tornado watch. Haunted by his past, Declan's never seen himself as a family man. But with Charlotte's brother depending on him and a baby on the way, maybe this is his chance to find out!